Managing Higher Education in the Post Fees Must Fall: Is the Centre Still Holding? - Sebake, B. K. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
The advent of #Feesmustfall has brought an era of the new dawn in the management of Higher Education in South Africa. This new dawn shifts power and authority from the universities' Senior Managements, which necessitates a radical shift in the manner in which Higher Education institutions are managed. It is arguable that the student activism has brought a new regime that is characterised by student revolutionary struggle in the current trajectory. The most fundamental question is the demarcation of roles between the student organisations, Student Representative Councils (SRC's), and Senior Management of the universities, as to whether the centre is still holding. The relationship of managing the universities requires a collegial relationship between Senior Management and SRC's, and it is the intention of this paper to assess the existence of this important relationship in daily management. The paper presents the observation and praxis in the management of institutions of higher learning, with literature review that forms part of the desk top analysis. It remains the qualitative in nature and repositioning the scientific nature of the art of management in a dynamic environment such as the university. Concepts such as; student politics and governance; protest and anarchy culture; good governance; management and administration; policy implications and the role of SRCs; leadership and democratic role of universities are amongst the areas of focus of this paper. The line of enquiry remains the diagnostic factor and remedies that aims at normalising higher education institutions as centres of excellence that provide hope. The paper is expected to produce a conclusion and recommendations that reflect steps to be taken in managing the current higher education in the midst of the growing activism that is persistently shifting powers and authority of Senior Management
Article published in the 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Good Governance; Leadership policy; Implications; Student politics; Political management and administration; Education, Higher--South Africa; Student movements--South Africa